DEFINING THE LAW FOR THE DISTRIBUTION OF AVERAGE MONTHLY EXPENDITURES IN THE ZARAFSHAN AND SURKHANDARYA RIVERS - Khanimkulov B. R. (Web of Journals Publishing, 2024)
In analytical groups, quantitative features are mainly used. They are also applied when constructing distribution rows. When grouping, on quantitative characteristics, questions arise about the number of groups and value - the width of the interval. These indicators are interconnected, the more groups are cut, the less the interval, and vice versa.
Keywords: water in the reservoir, full elections, incomplete elections, conditions of regularity Kramer-RAO, Fisher's information.